2022
DOI: 10.7759/cureus.28491
|View full text |Cite
|
Sign up to set email alerts
|

Smegma Pearl in a Circumcised Patient: A Case Report

Abstract: Smegma pearls, also called smegmomas, are a natural secretion composed of epithelial cells, protein, and fat. Smegma pearls are not carcinogenic and do not induce damage or irritation. Despite the frequent occurrence of smegma pearls in uncircumcised children, no case among circumcised patients was reported. Here, we are presenting, for the first time, a case of smegma pearl in a circumcised patient. A 36-year-old circumcised male patient presented with a smegma pearl. The purpose of the present case report is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Two patients in this series presented with a yellowish discharge under the penile skin bridge. This was smegma, which is commonly found in uncircumcised males, but Almutawa et al 11 reported this in a 36-yearold, circumcised male. Smegma is an opaque white or yellowish substance composed of dead cells and skin oils that is malodorous.…”
Section: Discussionmentioning
confidence: 96%
“…Two patients in this series presented with a yellowish discharge under the penile skin bridge. This was smegma, which is commonly found in uncircumcised males, but Almutawa et al 11 reported this in a 36-yearold, circumcised male. Smegma is an opaque white or yellowish substance composed of dead cells and skin oils that is malodorous.…”
Section: Discussionmentioning
confidence: 96%
“…In affected individuals, the prepuce exhibits a partial retractability while the urethra remains unaffected 1 . A diverse range of bacterial species may inhabit the preputial sac, thereby predisposing them to bacterial superinfection 4 . With regard to management, the primary therapeutic modality for smegma pearls involves offering reassurance and counseling to the patient, with the expectation that spontaneous separation will occur over time 2 …”
Section: Discussionmentioning
confidence: 99%
“…Smegma has a typical slimy odor, consisting of epithelial debris, fat, and proteins 3 . While smegma is not uncommon in uncircumcised boys, it is rare to occur in circumcised individual with only single case reported in literature 4 . In affected individuals, the prepuce exhibits a partial retractability while the urethra remains unaffected 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations